Pigeonpea sterility mosaic virus: a legume-infecting Emaravirus from South Asia - Patil, B.L.; Kumar, P. Lava (Wiley, 2015)
Pigeonpea sterility mosaic virus (PPSMV), a species of the genus Emaravirus, is the causal agent of sterility mosaic disease (SMD) of pigeonpea [Cajanus cajan (L.) Millsp]. This disease, dubbed the ‘green plague’, as the infected plants remain in the vegetative state without flower production, has been reported from India and a few other South-East Asian countries. SMD is estimated to result in an annual yield loss of over US$300 million in India alone. The aetiology of SMD, which remained a mystery for over 70 years, was resolved with the discovery of PPSMV in 2000 and its complete genome sequence in 2014